ISOVIST POLYGON IN REGARD TO VIEWING DISTANCE AS A REFERENCE FOR SOFTBALL STADIUM MOVEMENT SPACE ACHIEVEMENT - Putra, Heristama; Trisyanti, Lucia Ina (Border: Jurnal Arsitektur, 2025)
Stadium spatial planning should always include circulation access for all users. Circulation routes must be clearly differentiated for spectators, players, and stadium management. This separation of access is intended to prevent conflicts between different spatial functions. The circulation in question refers to entry and exit access within the softball stadium building. With the numerous access points and rooms in the facility, clear identification signs (signage) are essential to help users quickly understand their surroundings and navigate to their destinations. In terms of layout, the softball stadium includes several spaces and rooms designed to support all visitor activities. Generally, a good building must have better spatial pattern arrangement, this can be assessed by measuring the sight distance that affects the achievement of space for movement. As a primary requirement for a stadium where human movement in the building must be fast in circulation, access in and out is a crucial part. The method used to answer this problem uses isovist polygons, where the results of data analysis from previous studies are incorporated to determine sight distance through the point of achieving spatial syntax. If previous research produces connectivity, integrity, and clarity quantitatively through the study of space syntax in the softball stadium building. As a result, a computerized display pattern will be obtained for several sides of the softball stadium layout. Visibility, using recognition measurements using isovist polygons, measures the user reach within the softball stadium based on key points of user circulation.